Hydrothermally prepared graphene-titania nanocomposite for the solar photocatalytic degradation of methylene blue - Chang, Betty Yea Sze; Mehmood, Muhammad Shahid; Pandikumar, Alagarsamy; Huang, Nay Ming; Lim, Hong Ngee; Ab Rahman, Marlinda; Yusoff, Norazriena; Chiu, Wee Siong (Taylor & Francis, 2016)
Reduced graphene oxide–titania (rGO–TiO2) nanocomposites were prepared by hydrothermal method at different reaction temperatures and characterized by powder X-ray diffraction, transmission electron microscopy, micro-Raman spectroscopy, X-ray photoelectron spectroscopy, and photoluminescence spectroscopy techniques, respectively. The photocatalytic properties of the nanocomposites were investigated toward the degradation of methylene blue under natural sunlight. The rGO–TiO2 shows better photocatalytic activity due to the extended visible light absorption, excellent adsorptivity, and effective electron transfer process than the other controlled photocatalysts. In addition, rGO–TiO2 shows good sustainability after subjecting it to five consecutive cycles of photodegradation. This enhanced photocatalytic performance and good sustainability toward dye removal makes this rGO–TiO2 nanocomposite as a potential candidate for wastewater treatment in textile and dyeing industries.